Cloud removal in optical remote sensing imagery based on SAR-guided inpainting using deep learning - Dou, Kaijie (Nanyang Technological University, 2023)
With the development of high-resolution optical remote sensing satellite technology, optical satellite images are gradually widely used in navigation and positioning, agricultural investigation, environmental protection, disaster prevention and reduction, marine development, urbanization research and other fields. However, not all images can meet the requirements of intelligent information processing. One of the most important factors is the cloud contamination. Clouds not only block the ground scene, but also change the spectral and texture information of the image to a certain extent, causing many disadvantages to many links in the production of remote sensing image products. The existing methods based on multi-temporal or single image restoration are affected by the change of ground features and the lack of prior information, so it is difficult to restore the real ground feature information under the cloud. At the same time, the Synthetic Aperture Radar (SAR) is not affected by weather factors and can penetrate clouds. However, because it has special microwave imaging mechanism and does not contain color information, it is difficult to visually identify the required information from SAR image. Therefore, taking advantage of the fact that SAR can work in any weather conditions and optical images have high resolution, this dissertation proposes an optical image cloud removal method based on SAR data by deep learning.